PROSEDUR PEMBELIAN BAHAN BAKU PADA CAFE ESPRESSINO JAKARTA - May Vitha Rahmadhani; Febi Anggara; Ali Zulfikar (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Activities of a company have a workflow that meets standarisation. One of the things that Café Espressino Jakarta does is to carry out procedural activities for raw material purchases. The purpose of this study is to explain the procedures for purchasing raw materials at Café Espressino, South Jakarta. This research was conducted using a qualitative approach through data collection techniques in the forms of observation, interviews, and study comments. The results of this study indicate that the procedures for purchasing raw materials at Café Espressino Jakarta starts from checking the availability of raw materials, making a list of raw materials, providing a purchase budget, ordering or purchasing raw materials, to making a purchase report. Overall, the procedures carried out have been adjusted to the company’s existing conditions so that the employees can follow the procedures.